2021
DOI: 10.1177/0300060520977417
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory indicator levels in patients undergoing aortic valve replacement via median sternotomy with preoperative anxiety and postoperative complications: a prospective cohort study

Abstract: Objective This study was performed to evaluate the association of preoperative anxiety with inflammatory indicators and postoperative complications in patients undergoing scheduled aortic valve replacement surgery. Methods A prospective cohort study was performed. The Hamilton Anxiety Scale was used to assess preoperative anxiety. The serum white blood cell (WBC) count and concentrations of C-reactive protein, interleukin (IL)-6, and IL-8 were measured 1 day preoperatively and 3 and 7 days postoperatively. Pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…In addition, we found more severe anxiety symptoms as a marginally significant predictor of CRP levels on postoperative days 1-3, perhaps because depressive symptoms may affect the initiation of the acute inflammatory response to a greater extent than anxiety symptoms. Furthermore, our findings concur partially with a study on 73 patients who underwent aortic valve replacement that reported an association between clinically relevant anxiety symptoms before surgery and elevated CRP levels on postoperative day 3 [22]. However, in that study, no significant association was found 7 days post-surgery [22], and another study found an inverse as- Original article sociation between more severe anxiety symptoms before surgery and CRP levels 1 day after CABG, with no further significant associations until postoperative day 5 [23].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In addition, we found more severe anxiety symptoms as a marginally significant predictor of CRP levels on postoperative days 1-3, perhaps because depressive symptoms may affect the initiation of the acute inflammatory response to a greater extent than anxiety symptoms. Furthermore, our findings concur partially with a study on 73 patients who underwent aortic valve replacement that reported an association between clinically relevant anxiety symptoms before surgery and elevated CRP levels on postoperative day 3 [22]. However, in that study, no significant association was found 7 days post-surgery [22], and another study found an inverse as- Original article sociation between more severe anxiety symptoms before surgery and CRP levels 1 day after CABG, with no further significant associations until postoperative day 5 [23].…”
Section: Discussionsupporting
confidence: 91%
“…Additional analyses used depression and anxiety as binary variables. To obtain a more comprehensive understanding of the investigated associations and their dynamics, analyses were additionally performed with somatic depressive symptoms, cognitive depressive symptoms, and for two distinct postoperative periods; the latter also allowed comparison with previous studies [10,11,21,22]. To achieve this, instead of adding a time-by-depression or time-byanxiety interaction to the multivariable models, we explored whether depressive/anxiety symptoms predicted the initiation of the acute inflammatory response (postopera-…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most patients are anxious during the preoperative period as a natural reaction to unpredictable and potentially threatening situations [89,90]. It has been shown that a curved, rather than a simple linear relationship, exists between preoperative anxiety and postoperative complications; for instance, the incidence of postoperative complications was significantly lower in patients with mild anxiety than in those without anxiety or with moderate-to-severe anxiety [91][92][93]. Although such a conclusion is still controversial [94], it is possible that mild anxiety promotes adaptive actions to cope with jeopardizing stimuli, thereby improving postoperative outcomes [91,93].…”
Section: The Influence Of Preoperative Anxiety On Postoperative Outcomesmentioning
confidence: 99%